Personality Inventory for the DSM-5 (Brief Form) Predictors of Sexual Addiction. Issue 3 (2nd October 2019) - Pocknell, Victoria; King, Alan R.
Abstract: Sexual addiction risk may be elevated by personality maladjustment. The Personality Inventory for the DSM-5 (PID) was identified in the DSM-5 as an exemplar for future personality research. The brief form (DSM-5-BF) canvases the same domains, with concerns raised that it may underestimate levels of maladjustment. PID-5-BF associations were found in this national sample ( N = 428) with all five subscales of the Sexual Addiction Screening Test (preoccupation with sex, loss of control, relationship disturbance, affective disturbance, and Internet addiction). PID-5-BF personality maladjustment in this national survey sample appeared to increase the relative risks of elevated sexual addiction symptomatology.